EFEKTIVITAS CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Novita Letek Kumanireng; Yasinta Yenita Dhiki; Hilaria Melania Mbagho (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2024)
This study aims to determine the effectiveness of CTL learning on mathematics learning outcomes in social arithmetic material in class VII students at Simon Petrus Catholic Middle School for the 2022/2023 academic year. The type of research used is quantitative descriptive research. The population in this study were 17 students in class VII at Simon Petrus Catholic Middle School, and the sample in this study was 17 students in class VII at Simon Petrus Catholic Middle School. The sampling technique was saturated sampling. The data obtained from the research sample were in the form of the value of the results of the test results of learning mathematics. Data analysis was performed by using the One Sample Test. The results of the study show that: Based on SPSS calculations, with a total of 17 students at a significant level of 0.000. At the significant level, 5% from the table obtained sig. (2-tailed) 0.000 <0.05. Then the data from the t-test results can be concluded that Contextual Teaching and Learning is very effective on student learning outcomes in class VII SMPS Simon Petrus Catholic Middle School in the 2022/2023 Academic Year.